(untitled) (Revista Cocar, 2022)
O objetivo deste artigo é evidenciar relações da Transposição Didática Interna nas criações didáticas envolvendo jogos como recurso de ensino e aprendizagem em matemática. Apoiamo-nos na teoria da transposição didática e em pesquisas em nível de mestrado e doutorado e adotamos uma perspectiva qualitativa de cunho teórico-bibliográfico. De nossas análises, destacamos que mesmo que o professor consiga implementar seu texto de saber nos dois momentos da TDI, ocasionando a criação didática, esse movimento sozinho não garante a institucionalização do saber envolvido na atividade proposta, pois perpassa pela maneira que o jogo é concebido como ferramenta didática pelo professor para ensinar um dado objetos matemático. Portanto, vale ressaltar que a utilização de qualquer jogo requer intencionalidade didática, pois sem objetivos definidos, não há garantia de aprendizagem. Palavras-chave: Jogo; Transposição didática interna; Criações didáticas. Abstract The objective of this article is to highlight relationships of the Internal Didactic Transposition in didactic creations involving games as a resource for teaching and learning in mathematics. We rely on the theory of didactic transposition and on research at master’s and doctoral level and we adopted a qualitative perspective of theoretical and bibliographical nature. From our analysis, we highlight that even if the teacher manages to implement his text of knowledge in the two moments of TDI, causing the didactic creation, this movement alone does not guarantee the institutionalization of knowledge involved in the proposed activity, because it depends on how the game is conceived as a didactic tool by the teacher to teach a given mathematical object. Therefore, it is worth mentioning that the use of any game requires didactic intentionality, because without defined goals there is no guarantee of learning. Therefore, it is worth mentioning that the use of any game requires didactic intention, because without defined objectives, there is no guarantee of learning. Keywords: Game; Internal didactic transposition; Didactic creations.